Classification and characterization of beef muscles using front-face fluorescence spectroscopy. (February 2015) - Sahar, Amna; Dufour, Éric
Abstract: The objective of this study was to evaluate the potential of fluorescence spectroscopy to identify different muscles and to predict some physicochemical and rheological parameters. Samples were taken from three muscles ( Semitendinosus, Rectus abdominis and Infraspinatus ) of Charolais breed. Dry matter content, fat content, protein content, texture and collagen content were determined. Moreover emission spectra were recorded in the range of 305–400 nm, 340–540 nm and 410–700 nm by fixing the excitation wavelength at 290, 322 and 382 nm, respectively. The results obtained were evaluated by partial least square discriminant analysis and partial least square regression. Results of our research work show that front-face fluorescence spectroscopy and chemometrics offer significant potential for the development of rapid and non-destructive methods for the identification and characterization of muscles. Highlights: Fluorescence spectroscopy has been used to classify meat muscles. An attempt has been made to identify different beef muscles using fluorescence spectra. Beef muscles were classified according to their chemical and rheological characteristics. Determination of some physico-chemical parameters of beef muscles by fluorescence spectra